2011
DOI: 10.1007/s00213-011-2567-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PDE10A inhibitors on MK-801-induced immobility in the forced swim test

Abstract: The possibility to substitute PCP by MK-801 in this model indicates that the effect is mediated by their common mechanism of NMDA antagonism. PDE10A inhibitors similar to clozapine significantly antagonize the increase of immobility, suggesting a therapeutic potential for the treatment of negative symptoms. However, further validation of the model is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…The enhancement of immobility after chronic administration of PCP (Noda et al, 1995), MK-801 (Langen et al, 2012), and ketamine (Chatterjee et al, 2011a) has been used previously as a model for the negative symptoms of psychosis, such as flattening of affect and avolition. Our observations indicated that chronic administration of BM reduced the immobility duration in the forced swim test, akin to clozapine.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of immobility after chronic administration of PCP (Noda et al, 1995), MK-801 (Langen et al, 2012), and ketamine (Chatterjee et al, 2011a) has been used previously as a model for the negative symptoms of psychosis, such as flattening of affect and avolition. Our observations indicated that chronic administration of BM reduced the immobility duration in the forced swim test, akin to clozapine.…”
Section: Discussionmentioning
confidence: 99%
“…[55]. Additionally, PDE10A inhibition led to reversal of MK-801-induced immobility in a forced swim test model, proposed to mimic negative symptoms in scz, using mice at 1 mg/kg po [56]. Interestingly, a recent report showed 6 induced significant akathisia-like behavior in nhp at 3 mg/ kg but not 1 mg/kg (Fig.…”
Section: Mp-10mentioning
confidence: 89%
“…However, studies showing a deleterious effect of the repeated forced swim on cognitive tasks, such as the Morris water maze (Abel and Hannigan 1992, Rates 1998), novel object recognition (Yuen et al 2012), object location (Borsoi et al 2015a) and prepulse inhibition tests (Borsoi et al 2015a, b), contradict this successful strategy theory. On the other hand, immobility behavior in the forced swimming has been also related to schizophrenia negative symptoms, as apathy and lack of initiative (Langen et al 2012, Noda et al 1995, Porsolt et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Similar results were described after repeated administration of another NMDAR antagonist, MK-801 (0.2 mg/kg/day for 15 days i.p. ): an increase on the immobility time which was blocked by antipsychotics administration (Kawaura et al 2015, 2016, Langen et al 2012, Rundfeldt et al 2000. These data lead to the use of the increase in the immobility time in the forced swimming as a tool to evaluate affective flattening in schizophrenia animal models (Neill et al 2014) and even for the development of new drug candidates (Porsolt et al 2010).…”
Section: Introductionmentioning
confidence: 99%